Influence of electrodes' distance upon properties of intrinsic and doped amorphous silicon films for heterojunction solar cells. Issue 5 (3rd March 2014) - Brinkmann, Nils; Gorgulla, Angelika; Bauer, Anja; Skorka, Daniel; Micard, Gabriel; Hahn, Giso; Terheiden, Barbara
<x xml:space="preserve">Abstract</x> In this work, the influence of electrodes' distance upon the properties of amorphous silicon (a‐Si:H) deposited by plasma‐enhanced chemical vapor deposition method on both intrinsic and doped a‐Si:H films is investigated in terms of their electrical, optical, and structural characteristics. For this purpose, Fourier‐transform infra‐red and secondary‐ion mass‐spectroscopy as well as photoconductance decay, spectral ellipsometry, and conductivity measurements are employed. Electrodes' distance is varied from 20 to 120 mm. Regarding the passivation quality of the a‐Si:H film an optimum electrodes' distance of 60 mm is found. In addition, electrodes' distance is detected to have a great influence on the accelerated initial growth rate, which strongly diminishes with increasing distance. Thus, electrodes' distance also determines the overall thickness of thin intrinsic a‐Si:H films being particularly interesting for utilization in heterojunction solar cells. With doped a‐Si:H films, however, electrodes' distance influences mainly the dopant concentration in the films and therewith their conductivity.